Metabólitos secundários, composição química e atividade antioxidante do óleo essencial e das folhas de Vitex megapotamica (Sprengel) Moldenke - Brum, Thiele Faccim de (2012)
The Verbenaceae family consists of about 2600 species, of which the genera Vitex has 250 species. Vitex megapotamica is distributed in northeastern Argentina, eastern Paraguay, in Uruguay and commonly found in southern Brazil. The present work aims to perform a phytochemical study, the chemical composition and antioxidant activity of essential oil and extracts of leaves of V. megapotamica. Leaves of V. megapotamica were collected in Santa Maria, RS, Brazil, in december of 2010. A dried voucher specimen is preserved in the herbarium of the Department of Biology at Federal University of Santa Maria by register number SMBD 13071. The material was macerated in ethanol (70%) and filtered, after a part of the ethanol extract was reserved and the other evaporated in rotary evaporator to remove ethanol (aqueous extract). This was partitioned in ampoules of separation using increasingly polar solvents: dichloromethane, ethyl acetate and butanol, and the crude extract was obtained by drying the aqueous extract. The phytochemical study revealed the presence of anthocyanins, phenols, tannins, catechins, flavonols, flavanones, flavanonóis, xanthones, triterpenoids, steroids, cardioactive glycosides, phenols with ortho and meta position free, coumarins and organic acids. The crude extract and fractions were investigated for antioxidant activity by the method of DPPH, TBARS and protein carbonyls, the content of phenolic compounds (flavonoids, polyphenols and tannins) was determined, and was performed to identification and quantification of phenolic acids by HPLC. The phenolics compounds were higher in the ethyl acetate fraction, being 522.4 ± 12.1 mg/g for polyphenols and 220.48 ± 0.30 mg/g for flavonoids, only this fraction showed condensed tannins, though in small quantity. The assays with DPPH revealed high radical scavenging capacity, showed IC50 ranged from 14.17 ± 0.76 μg/ml to 37.63 ± 0.98 μg/ml. The crude extract and fractions inhibited the TBARS production, with IC50 ranging from 16.36 ± 5.09 μg/ml to 72.72 ± 7.22 μg/ml, where as ethyl acetate fraction was showed the best result. The extracts were effective in inhibiting protein carbonyls at concentrations of 50, 100 and 200 mg/ml, therefore have a higher amount of phenolic compounds. HPLC analysis revealed the presence of chlorogenic and rosmarinic acids and the second in the greatest quantity. Through the extracting the essential oil of the leaves, it was obtained the chemical composition and antioxidant capacity by DPPH method. The main components in the oil were BHT (34.17%), phytol (12.66%), α-caryophyllene (11.84%), δ-elemene (10.65%), β-caryophyllene (7.82%), γ-elemene (4.24%) and germacrene D (2.82%). The oil showed percentage inhibition of 35.62% and 75.25% at concentrations of 76 and 101.6 mg/ml, respectively. Probably, the antioxidant activity reported is due to the major component of BHT. Through this study it was possible identify the chemical composition of essential oil, as well as know the major groups of substances present in extracts from leaves of V. megapotamica who obtained a good antioxidant activity.